If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + 4 = 0 Reorder the terms: 4 + n = 0 Solving 4 + n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + n = 0 + -4 Combine like terms: 4 + -4 = 0 0 + n = 0 + -4 n = 0 + -4 Combine like terms: 0 + -4 = -4 n = -4 Simplifying n = -4
| 3r+4+3r=10 | | 8n-6+2n=14 | | 25y^2-80y+6= | | -3p+2p=4 | | 3x+17=32 | | k+4+3=1 | | 1.5c+c=20 | | x+1+6=6 | | k+7+8=19 | | 3x+2-6x=-7 | | -3m-8m=-11 | | -5x+x=4 | | -5n+3n=-10 | | 65-6X=12X+19 | | 9u^2-36v^2= | | 4+2a+6a=12 | | 4*x=60 | | 2n+5n=-21 | | 75x^3-12x=0 | | 49y^2-28y+4= | | v+1+4=10 | | m^3+6m^2-4m=0 | | a^2+8a-15=0 | | 116-4x=23x+17 | | ln(13)+ln(x)=0 | | 7b+1-b=1 | | x+7=-2(4x+10) | | 7-9x=46-30x | | 184-4x=41x+19 | | 6+x=-13 | | -42+y+2=44 | | y^2+6y-7=17 |